Estimation of Optimum Main Engine Power for a 14.5 m Wooden Purse Seine Vessel (Case Study of Motor Vessel (MV) Putra Abadi) - Fis Purwangka; Daisy Rahma Rizal; Mohammad Imron; Sugeng Hari Wisudo (International Journal of Marine Engineering Innovation and Research, 2024)
Small pelagic purse seine vessels in Jakarta are dominated by vessels with a length of 14.5 m. The vessel's hull construction was made by a traditional vesselyard using wood. The construction process only relies on the skills and habits of craftsmen. The choice of engine is only based on the size of the vessel and the price of the engine without calculating resistance. In general, the power of the purse seine main engine as the main mover is not suitable, causing wasteful fuel consumption. The fishing vessel engine used by MV Putra Abadi comes from a modified truck engine so that the fuel used does not comply with specifications. This research aims to determine the amount of power needed to move a Putra Abadi fishing vessel. The method used is direct observation by taking direct measurements of the dimensions of MV Putra Abadi. Next, the engine resistance and power are also calculated using the Holtrop resistance method in software. The Putra Abadi fishing vessel based on hydrostatic calculations showed that the block coefficient (Cb) is 0.425 at a speed of 7 knots, the resulting resistance is 2.5 kN. While at a maximum speed of 8 knots the BHP is 98.82. The power requirement of Putra Abadi fishing vessel according to this calculation is only 46% of the engine power currently used.